Strategi Cyber Public Relation dalam Membangun Reputasi Brand di Era Digital: Pendekatan Interaktif Melalui Media Sosial - Hapsari, Meyta Indah; Alfraita, Ariyan (Universitas Pahlawan Tuanku Tambusai, 2025)
This article explores the strategic role of Cyber Public Relations (Cyber PR) in shaping image and maintaining organizational reputation in the digital era. This approach utilizes modern communication technologies, especially social media, to create broader and more responsive public engagement. The study employs a qualitative method with a literature review approach based on various reputable national academic journals. The findings indicate that Cyber PR is not merely a promotional tool, but a key instrument in building trust and long-term relationships with the public. Challenges such as misinformation, digital reputation crises, and public transparency demands are prominent issues, yet can be addressed through adaptive and data-driven communication strategies. Simultaneously, the opportunities provided by digital media such as message virality, communication personalization, and digital collaboration become major strengths for PR practitioners. In conclusion, Cyber PR is an essential and integral tool for building effective and sustainable organizational communication in the modern public communication landscape.